2015
DOI: 10.1515/hukin-2015-0090
|View full text |Cite
|
Sign up to set email alerts
|

Game Performance Evaluation in Male Goalball Players

Abstract: Goalball is a Paralympic sport exclusively for athletes who are visually impaired and blind. The aims of this Additional anthropometric measurements included body mass (kg), body height (cm), the arm span (cm) and length of the body in the defensive position (cm). The results differentiating both groups showed that the players with total blindness obtained higher means than the players with visual impairment for game indicators such as the sum of defense (p = 0.03) and the sum of good defense (p = 0.04). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
33

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 19 publications
3
36
0
33
Order By: Relevance
“…Few studies have demonstrated physical responses by goalball athletes during a laboratory condition, field tests, and/or a game context. In the LaB, the majority of studies investigate the morphological profile ( Çolak et al, 2004 ; Scherer et al, 2012 ), anthropometric measurements ( Calıskan et al, 2011 ; Molik et al, 2015 ), and general physical fitness ( Çolak et al, 2004 ; Karakaya et al, 2009 ; da Cunha Furtado et al, 2016 ). Gulick and Malone (2011) were the first authors to compare aerobic fitness in female goalball athletes obtained during the LaB condition (i.e., incremental test) to those observed during a field test, similar to a beep test, but performed on the goalball court.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have demonstrated physical responses by goalball athletes during a laboratory condition, field tests, and/or a game context. In the LaB, the majority of studies investigate the morphological profile ( Çolak et al, 2004 ; Scherer et al, 2012 ), anthropometric measurements ( Calıskan et al, 2011 ; Molik et al, 2015 ), and general physical fitness ( Çolak et al, 2004 ; Karakaya et al, 2009 ; da Cunha Furtado et al, 2016 ). Gulick and Malone (2011) were the first authors to compare aerobic fitness in female goalball athletes obtained during the LaB condition (i.e., incremental test) to those observed during a field test, similar to a beep test, but performed on the goalball court.…”
Section: Discussionmentioning
confidence: 99%
“…The official game comprises two halves of 12 min with three teammates on each side of the court, who successively perform offensive and defensive actions ( Morato et al, 2012 ). The majority of studies with goalball players have examined functional, anthropometric, and morphological evaluation aspects ( Çolak et al, 2004 ; Karakaya et al, 2009 ; Calıskan et al, 2011 ; Scherer et al, 2012 ; Molik et al, 2015 ; da Cunha Furtado et al, 2016 ). Other studies analyzed aerobic parameters in field tests ( Çolak et al, 2004 ; Karakaya et al, 2009 ; Gulick and Malone, 2011 ; da Cunha Furtado et al, 2016 ), and technical-tactical performances in tests or during the game ( Stamou et al, 2007 ; Bowerman et al, 2011 ; Morato et al, 2012 , 2017 , 2018; Molik et al, 2015 ; Link and Weber, 2018 ; Monezi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical research analysed different shot techniques and their impact on ball speed [ 9 ]. Other studies focussed on physical properties of the ball [ 10 ], physiological load during matches [ 11 ], anthropometric characteristics of top level players [ 12 , 13 ], requirement profiles for goalball coaches [ 14 ], and provided guidance for teaching in schools [ 15 ]. In addition, goalball-specific testing methods were developed for auditory perception [ 16 ] and endurance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Análises táticas geralmente fornecem resumo dos resultados de desempenho (por exemplo, posicionamento de defesa, distribuição de arremessos, etc. ), praticas frequentes no basquete 37,44 e rugby em cadeira de rodas 45,46 e no goalbaal 47,48 . Outro ponto a ser destacado nas análises de desempenho esportivo se concentra na escolha dos jogadores que vão constituir a equipe.…”
Section: Sumário De Resultadosunclassified